A comprehensive investigation of the influence of clay minerals on oxidized and pyrolyzed cokes in in situ combustion for heavy oil reservoirs. (15th October 2021) - Li, Yi-Bo; Lin, Xiang; Luo, Chen; Hu, Zhi-Ming; Jia, He-Fei; Chen, Ju-Tao; Pu, Wan-Fen
Graphical abstract: Highlights: The clay minerals had a catalytic effect on the generation and reaction of coke. Montmorillonite and kaolinite possessed catalytic on the generation of oxidized coke. Montmorillonite can cause the coke reaction at relatively low-temperature ranges. The four clays can promote the reaction of the pyrolyzed coke at different degrees. Abstract: Coke is the most important intermediate product during an in situ combustion for maintaining the combustion front stability. Coke is classified as oxidized and pyrolyzed based on the reaction mechanism. The clay minerals exhibit a catalytic effect on the formation and reaction of coke. In this study, a comprehensive experiment was performed to investigate the influence of four clay minerals on oxidized and pyrolyzed cokes. Results showed that these clay minerals exhibited a catalytic effect on the generation and reaction of coke at different levels. In the oxidation process montmorillonite and kaolinite exhibited an excellent catalytic effect on the generation of oxidized coke. In the pyrolysis process, montmorillonite, kaolinite, and illite could promote the breakage of C–S, C–N, and C–O bonds and reduce the number of heteroatoms. In the reaction process, the catalytic effect of montmorillonite induced the aggravation of the polymerization of hydrocarbon derivative with a large molecular weight, resulting in a low activity of the oxidized coke. Moreover, the montmorillonite can induce coke reaction in a low-temperature range, whereas the others exert only suppression effects on coke decomposition. The pyrolyzed coke achieves lower activation energy than the oxidized coke, proving that the pyrolyzed coke can be easily ignited under the reservoir condition. All clay minerals investigated herein can promote the reaction of pyrolyzed coke to different degrees. The montmorillonite achieves the lowest activation energy at 35 °C–100 °C and 350 °C–600°C stages, which benefits the movement of the combustion front.